Publications control in South Africa - H.L. Venter (Communicare)
The South African publications control system has, during the past two to three years, shown much greater tolerance than it has been given credit for. To Jessen negative perceptions, the public should be infonned about the current state of affairs and the concessions already made in the current application of the existing legiSlation. This article also provides details of arguments considered during the drafting of the new Film and Publications Bill, aswell as details of, and comments on the proposed procedures with regards to future classification of publications and films. The meaning and effect of claSSifications, age restrictions and new proposals such as adult premises, are also explained.